Study of Z Boson Production in PbPb Collisions at √S(NN)=2.76 TeV. - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Erö, J; Fabjan, C; Friedl, M; Frühwirth, R; Ghete, V; et al. (2011)
A search for Z bosons in the μ(+)μ(-) decay channel has been performed in PbPb collisions at √S(NN)=2.76  TeV with the CMS detector at the LHC, in a 7.2 μb(-1) data sample. The number of opposite-sign muon pairs observed in the 60-120 GeV/c(2) invariant mass range is 39, corresponding to a yield per unit of rapidity (y) and per minimum bias event of [33.8±5.5(stat)±4.4(syst)]×10(-8), in the |y|<2.0 range. Rapidity, transverse momentum, and centrality dependencies are also measured. The results agree with next-to-leading order QCD calculations, scaled by the number of incoherent nucleon-nucleon collisions.